Phylogeny and taxonomic revision of Deronectina Galewski, 1994 (Coleoptera: Dytiscidae: Hydroporinae: Hydroporini) - Fery, Hans; Ribera, Ignacio (Zootaxa, 2018)
The subtribe Deronectina Galewski, 1994 (Dytiscidae, Hydroporinae, Hydroporini) is distributed in the Nearctic, in the north of the Neotropical region, and in the Palaearctic and Afrotropical regions. It is currently composed of 194 species and 13 subspecies in eight genera: Amurodytes Fery & Petrov, 2013, Boreonectes Angus, 2010, Deronectes Sharp, 1882, Nebrioporus Régimbart, 1906, Oreodytes Seidlitz, 1887, Scarodytes Gozis, 1914, Stictotarsus Zimmermann, 1919, and Trichonectes Guignot, 1941. We present a morphological and a molecular phylogeny of the species of the subtribe, and a revision of their taxonomy to accommodate our phylogenetic results. The morphological phylogeny is based on the study of 54 characters of the adults of 189 species and 2 subspecies, of which 114 species and the 2 subspecies were coded in the morphological matrix. For the molecular phylogeny we investigated 115 species and 11 subspecies, using a combination of fragments of four mitochondrial (COI, 16S rRNA, tRNA-Leu and NAD1) and two nuclear genes (18S rRNA and H3), analysed with maximum likelihood and Bayesian methods. For both datasets we included the type species of all genus-group taxa. The morphological, molecular and combined phylogenies mostly agree with the current classification of the group, but in some cases our results are in contradiction with established genera. Most remarkable are the polyphyly of Stictotarsus and Nebrioporus, the low support for the monophyly and internal phylogeny of Oreodytes, and the low support for the monophyly of Deronectina with molecular data. Thus, we introduce some taxonomic changes in the current classification to accommodate the generic concepts to our phylogenetic results. Nine new genera are established: Clarkhydrus n. gen. (type species Hydroporus roffii Clark, 1862), Hornectes n. gen. (type species Hydroporus quadrimaculatus Horn, 1883), Iberonectes n. gen. (type species Deronectes bertrandi Legros, 1956), Larsonectes n. gen. (type species Potamonectes minipi Larson, 1991), Leconectes n. gen. (type species Hydroporus striatellus LeConte, 1852), Mystonectes n. gen. (type species Deronectes neomexicanus Zimmerman & Smith, 1975), Nectoboreus n. gen. (type species Hydroporus aequinoctialis Clark, 1862), Nectomimus n. gen. (type species Oreodytes okulovi Lafer, 1988), and Zaitzevhydrus n. gen. (type species Hydroporus formaster Zaitzev, 1908). Three genera are reinstated as valid: Deuteronectes Guignot, 1945 (stat. rest.) (type species Hydroporus picturatus Horn, 1883), Nectoporus Guignot, 1950 (stat. rest.) (type species Hydroporus abbreviatus Fall, 1923), and Neonectes J. Balfour-Browne, 1940 (stat. rest.) (type species Hydroporus natrix Sharp, 1884). Thirty-six new combinations for species and subspecies thus far treated in the genera Boreonectes, Nebrioporus, Oreodytes and Stictotarsus result from the new classification: Clarkhydrus corvinus (Sharp, 1887) n. comb., C. decemsignatus (Clark, 1862) n. comb., C. deceptus (Fall, 1932) n. comb., C. eximius (Motschulsky, 1859) n. comb., C. falli (Nilsson, 2001) n. comb., C. interjectus (Sharp, 1882) n. comb., C. minax (Zimmerman, 1982) n. comb., C. opaculus (Sharp, 1882) n. comb., C. roffii (Clark, 1862) n. comb., C. spectabilis (Zimmerman, 1982) n. comb., Deuteronectes angustior (Hatch, 1928) n. comb., Hornectes quadrimaculatus (Horn, 1883) n. comb., Iberonectes bertrandi (Legros, 1956) n. comb., Larsonectes minipi (Larson, 1991) n. comb., Leconectes striatellus (LeConte, 1852) n. comb., Mystonectes coelamboides (Fall, 1923) n. comb., M. grammicus (Sharp, 1887) n. comb., M. neomexicanus (Zimmerman & Smith, 1975) n. comb., M. panaminti (Fall, 1923) n. comb., M. titulus (Leech, 1945) n. comb., Nectoboreus aequinoctialis (Clark, 1862) n. comb., N. dolerosus (Leech, 1945) n. comb., N. funereus (Crotch, 1873) n. comb., Nectomimus okulovi (Lafer, 1988) n. comb., Nectoporus angelinii (Fery, 2015) n. comb., N. congruus (LeConte, 1878) n. comb., N. crassulus (Fall, 1923) n. comb., N. obesus obesus (LeConte, 1866) n. comb., N. obesus cordillerensis (Larson, 1990) n. comb., N. rhyacophilus (Zimmerman, 1985) n. comb., N. sanmarkii sanmarkii (C.R. Sahlberg, 1826) n. comb., N. sanmarkii alienus (Sharp, 1873) n. comb., N. sierrae (Zimmerman, 1985) n. comb., N. subrotundus (Fall, 1923) n. comb., Zaitzevhydrus formaster formaster (Zaitzev, 1908) n. comb., and Z. formaster ulanulana (C.-K. Yang, 1996) n. comb.